Attitude, knowledge and competency towards precision agricultural practice among paddy farmers - Abdullah, Johari; Ahmad, Shamsuddin; Ismail, Ismi Arif (Universiti Putra Malaysia Press, 2012)
Previous research indicated that farmers’ attitude, knowledge and competency influenced the adoption of technology. Realizing the truth, this study was carried out with the purpose to find factors and answers to questions that influenced the adoption of Precision Agricultural Practice (PAP). The study was carried out on 119 paddy farmers at IADA Barat Laut, Selangor. Results indicated that attitude, knowledge and competency significantly influenced the adoption of the PAP. Hence, to change the farmers’ attitude, knowledge and competency are vital aspects in the adoption of the PAP.